Beginning reading in English a proposed scope and sequences and sample lessons - Raquepo, Crisanta L. 1934- ([Quezon City s.n.], 1967)
The aim of the study is to construct a series of lessons designed for Filipino children who are starting to read in English after one and a half or two years of reading in the vernacular and listening and speaking English. This is geared towards the development of basic comprehension skills in addition to word attack skills.
Thesis (M.A.T.Reading)--University of the Philippines
Keywords: Reading